Kinematics of unanticipated cutting maneuver in female soccer players after 2 competitive matches - Snyder, B.; Aarts, H.; Shoultz, E.; Mitric, I.; Singerman, A.; Trone, S. (The Journal of Strength and Conditioning Research, 2021)
Muscular fatigue is known to affect lower-limb kinematics, which may increase the risk of ligament injury. Female soccer athletes have been identified as having an increased risk of anterior cruciate ligament (ACL) injuries. Purpose: The purpose of this study is to analyze changes to kinematic ACL risk factors due to muscular fatigue incurred in multiple Division 1 women's collegiate soccer games separated by less than 48 hours. Methods: Twelve Division 1 female soccer players were recruited for this study and joint kinematics were measured during a jump-landing and sidestep maneuver. A group of 7 players who traveled more than 9.5 km were included in the study. Before and after each match, reflective markers were affixed at specific anatomical locations. Each player jumped off a 12-inch box and performed an unanticipated sidestep maneuver, indicated mid-jump by a randomized computer algorithm. The jumps were assessed using an 8-camera motion capture system, digital gate timers, and a force plate to measure Ground Reaction Forces. This protocol was performed at the following time points: before the first match (T0), immediately after the first match (T1), 12 hours after the first match (T2), immediately after the second match (T3) and 65 hours after the second match (T4). Results: Significantly lower knee flexion at initial contact was shown at T3 (13.64° ± 3.3 SD) compared to T1 (15.56° ± 3.4, p = 0.027), which has been associated with a greater risk of injury. However, maximum knee flexion was significantly higher at T3 (75.5° ± 10.8) compared to T1 (71.6°10.5), which could reflect knee extensor fatigue. Max knee valgus peaked after the first match (T1 = 4.772° ± 4.9), but was only significantly decreased at T4 (2.709° ± 4.2, p = 0.044), indicating the importance of time to recover from fatigue incurred in games. Conclusions: These findings suggest that match play alters knee kinematics and these differences may not return to normal after one match. Practical Application: Athletic trainers and strength and conditioning professionals should be aware that fatigue elevates injury risk, especially when playing multiple soccer games with short recovery periods.